2017
DOI: 10.1016/j.mri.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

A non-contrast CMR index for assessing myocardial fibrosis

Abstract: Purpose: Safe, sensitive, and non-invasive imaging methods to assess the presence, extent, and turnover of myocardial fibrosis are needed for early stratification of risk in patients who might develop heart failure after myocardial infarction. We describe a non-contrast cardiac magnetic resonance (CMR) approach for sensitive detection of myocardial fibrosis using a canine model of myocardial infarction and reperfusion. Methods: Seven dogs had coronary thrombotic occlusion of the left anterior descending coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…However, mFI values were significantly different between animals with mild DD and animals with moderate DD as well as between HCs and animals with mild DD. A recent animal study [14] provided additional evidence that mFI has a greater sensitivity for detecting diffuse types of myocardial fibrosis as compared with T1ρ in dogs with myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, mFI values were significantly different between animals with mild DD and animals with moderate DD as well as between HCs and animals with mild DD. A recent animal study [14] provided additional evidence that mFI has a greater sensitivity for detecting diffuse types of myocardial fibrosis as compared with T1ρ in dogs with myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the increase is modulated by the chemical shifts and exchange rates of the macromolecules. The higher sensitivity of mFI to the changes in collagen content may be due to the cancelation of intrinsic T2, thereby resulting in an amplified effect of the chemical exchange during the relaxation times, when water protons to exchange are locked without dephasing [14]. It was noted previously that mFI represents the subtraction of two T1ρ images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other native quantification techniques, T 1ρ improves the contrast ratio between diseased and healthy myocardial tissue [16][17][18]. In experimental models as well as in vivo, T 1ρ has already been shown to be a sensitive marker for the detection of several tissue damages like edema, ischemia, fibrosis and myocardial infarction [19][20][21][22]. Moreover, T 1ρ gives the possibility for dispersion measurements by manipulation of the effective SL pulse amplitude, enabling additional contrast mechanisms and further improved tissue characterization [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, T 1ρ gives the possibility for dispersion measurements by manipulation of the effective SL pulse amplitude, enabling additional contrast mechanisms and further improved tissue characterization [11]. In this context it could already be shown that T 1ρ dispersion quantification can be used as a myocardial biomarker for the classification of different stages of fibrosis [19]. This dispersion behavior is of great interest and might be highly beneficial not only in basic research in various animal models, but also in various scenarios in clinical practice [23][24][25].…”
Section: Introductionmentioning
confidence: 99%